23 Surveillance and Incidence of Chemotherapy-Induced Cardiotoxicity in Breast Cancer: A Long Term Observational Study. (3rd June 2016) - Soujeri, Bayan; Singh, Jagdeep; Chew, Samuel; Hawkey, Sean; Ferguson, Michelle; Lang, Chim C
Abstract : Introduction: Recent advances in chemotherapy have transformed breast cancer from a fatal disease to a survivable condition. However, many patients who survive their cancer, succumb to the unintended adverse effects of therapy. Chemotherapy-induced cardiotoxicity is now among the most feared adverse effects and has been reported in up to 50% of patients up to twenty years later, the majority of which occurring after completion of therapy. Consequently, current breast cancer treatment guidelines recommend assessment of LV function before, during and after chemotherapy. Methods: We conducted a retrospective cohort study of 1263 breast cancer patients who received either anthracyclines alone or combined with the monoclonal antibody trastuzumab at Ninewells Hospital, Dundee between January 2003 and December 2014. Imaging modalities such as MUGA scans were extracted from the CHEMOCARE database which allowed us to identify whether cardiac assessments were carried out at baseline and during treatment as per recommendations. LVEF at baseline and during routine follow-up was also calculated to determine if patients had developed left ventricular systolic dysfunction (LVSD) during chemotherapy. Results: Of 1262 patients, 1260 patients (99.8%) were female, with an mean age of 59.3 years. 82.2% of the patients had received anthracyclines alone and 17.8% received a combination of an anthracycline and trastuzumab. 900 patients (71.3%) received adjuvant radiotherapy, 311 (24.6%) received chemotherapy only and 51 (4.0%) had an unknown type of therapy. 1101 (87.2%) of patients were on epirubicin with an average cumulative dose of 570.7 mg/m 2, making it the most used anthracyline as it is less cardiotoxic compared to doxorubicin. 683 (54.0%) underwent screening for baseline cardiac function using MUGA scans. Of these, only 290 (42.5%) had follow up scans during the course of their treatment as mandated by guidelines. Among patients who had adequate follow up, 32 (11%) developed LVSD during chemotherapy, corresponding to a rate of 6.7% (n = 5) among those on anthracyclines alone and 12.5% (n = 27) among patients on combination therapy. Conclusion: Despite recommendations to monitor cardiac function, our data shows in all chemotherapy patients, only half of them were monitored in our cohort. Although LVSD is usually a late sequel of cancer treatment, we have shown its occurrence even when chemotherapy is being delivered, thus highlighting the importance of surveillance to ensure early detection and management. This may reflect physicians' opinion, contrary to guideline recommendations, that single chemotherapy is associated with less cardiotoxicity.